Perencanaan Infrastruktur Gedung Kantor Dengan Konsep Rumah Betang Modern Untuk Optimalisasi Pelayanan - Muhammad Nanda Arya Putra; Mei Yuliani; Reynaldo Kristy; Dela Meinita; Daniel Delon Tilaar; Desi Riani (Fakultas Teknik Universitas Palangka Raya, 2025)
Pahandut Subdistrict, as the primary activity center in Palangka Raya City, faces public service constraints due to inadequate physical office conditions to accommodate high visitor volumes. This community service activity, conducted through the